Pengaruh Pelatihan Dan Kompetensi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Pariwisata Pemuda Dan Olahraga Kabupaten Agam - Fadila, Rizka (Riset Sinergi Indonesia, 2024)
The Agam Regency Youth and Sports Tourism Office (Dispapora) is a regional apparatus for the implementation of government affairs that is under the authority of the region, led by the head of the agency who is subordinate and accountable to the Regent through the Regional Secretary. The purpose of this training is to find out and analyze the influence of training and Competency on Employee Performance with Job Satisfaction as an Intervening Variable. The research method used is quantitative research. The number of samples was 75 respondents and used SEM analysis tools with SmartPLS 3. In the data collection technique in this study, by distributing the questionnaire using the Likert scale. The results of the study show that directly the most dominant variable, namely training, has a positive and significant effect on job satisfaction. Therefore, as evidenced by the increasing number of training promised by the company, employee job satisfaction will increase. While the indirect influence for the most dominant variable states that Training has a positive and significant effect on Employee Performance through Job Satisfaction. If the training is implemented properly, then employee performance can be even better, and employees will feel satisfied with the work they have done, so that the level of job satisfaction in the company will also increase